Design and Usability Testing of an Augmented Reality (AR) Environment in Pharmacy Education-Presenting a Pilot Study on Comparison between AR Smart Glasses and a Mobile Device in a Laboratory Course - Karmen Kapp; Mia Sivén; Patrick Laurén; Sonja Virtanen; Nina Katajavuori; Ilona Södervik (MDPI AG, 2022)
An essential feature of pharmacy education is the teaching of theoretical knowledge with the support of practical work in the laboratory. When properly utilized, laboratory activities have the potential to enhance students' achievement, conceptual understanding, and positive attitudes towards learning. In this pilot study, an augmented reality (AR) environment was designed and introduced for teaching laboratory skills in pharmacy education at the university level. The AR environment was used by pharmacy students (n = 36), featuring gate questions, information screens, Quick Response codes, think-aloud questions, and instant feedback. The environment was utilized with smart glasses and mobile devices with the aim of comparing the support to students' performance. User experience was evaluated through self-efficacy beliefs and anxiety towards the technology. As a result, students found the environment a useful supplement to traditional laboratory teaching. Smart glasses and mobile devices were both accepted with great positivity but neither being clearly preferred over the other. Smart glasses were noted to provide sufficient feedback in the right stages of work. In contrast, mobile devices promoted the learning process more than the smart glasses. The self-efficacy results for mobile device use were higher, especially related to device handling and operating the AR environment. The pilot study gives educators valuable insights on the usability of AR technology in guiding laboratory tasks, although future work should involve larger and more diverse samples, as well as different learning tasks.